Formação de agregados de líquidos iônicos dicatiônicos derivados do imidazolíneo em água - Gindri, Izabelle de Mello (2013)
This paper presents the study of influence of molecular structure of ionic liquid-type Gemini imidazolium ìn the formation of aggregates in aqueous solution. The aggregation behavior was investigated through differential scanning calorimetry, conductivity, surface tension, fluorescence, dynamic light scattering techniques and transmission electron microscopy. Among the obtained data, it is possible to highlight the critical aggregation concentration (cac) determination, that is, a concentration range where a variation in physical and chemical properties of the solution emerging from the formation of aggregates can be observed. Differential scanning calorimetry showed that the aggregation can be detected by means of thermal events, characteristics of pure LI. Through the conductivity, it was possible to determine thermodynamic parameters, as the aggregate free energy (ΔG°a), the binding degree of the counterion to the aggregate (α), and the process equilibrium constant (Ka). Surface tension measurements provided data regarding the activity of the surfactant LI studied, while fluorescence, dynamic light scattering and transmission electron microscopy were important to obtain information on the aggregates' size. Critical packing parameter was determined throughout data obtained from X-ray diffraction and surface tension. This parameter allowed the prediction of LI micellar form currently in study. It was observed that the values of cac determined by the methods employed are consistent with each other and it was found that the increase of the carbon chain used as a spacer group promoted the aggregates formation, as well as caused an improvement in the surfactant LI properties.